Payment Fintechs and Debt Enforcement - Kumar Rishabh; Jorma Schäublin (University of Basel, Center of Business and Economics (WWZ), 2021)
Payment fintechs, acting as lenders, possess a potential solution to weak debt enforcement because of their ability to deduct a part of a merchant's digital sales towards loan repayment. Analyzing payments processed by an Indian fintech company offering sales-linked loans, we find that some borrowers discontinuously reduce sales flowing through the company immediately after the loan disbursal to circumvent repayment and strategically default. Using credit bureau scores sourced independently and the spatial and temporal heterogeneity in cash availability generated by a cash-crunch episode, we find that competition from other lenders and cash limits the effectiveness of this enforcement technology
Keywords: G20; G21; G23; 330; Fintech lending; limited enforcement; sales manipulation; regression discontinuity